Breaking free of the neoliberal paradigm: refocusing the lens for social work and the social work curriculum in Aotearoa New Zealand (part II). Issue 3 (2nd April 2020) - Fraser, Sarah; Briggs, Lynne
ABSTRACT: This article is the second of two detailing the outcomes of an extensive study exploring a largely unrecognised role for social workers as educators in their everyday practice in Aotearoa New Zealand. The first focused on the quantitative aspect of the study. The second, smaller phase of the study is discussed in this article. In a series of semi-structured interviews, social workers from a range of settings and positions shared short narratives describing their practice. While their accounts gave clear examples of undertaking educative tasks in their everyday practice, the social workers did not always recognise them as such. In addition, content analyses showed that the role is hardly recognised in position descriptions, and educational theory and practice skills are not included in the Social Work Registration Board's requirements for curricula for professional programmes. It is considered that making the role explicit and incorporating education theory into the social work curriculum would create an opportunity to refocus the lens for practice away from the current pervasive neoliberal paradigm. The article concludes by arguing that, as is being considered in a number of western countries, the European discipline of social pedagogy has much to offer in this endeavour.